The influence of knowledge-sharing, business strategy alignment and long-term relationships on supply chain performance in the small and medium enterprise sector - Mofokeng, Teboho Mantebele (My University, 2015)
The purpose of this study was to investigate the influence of knowledge-sharing, business strategy alignment and long-term relationship orientation on supply chain performance in the Small and Medium Enterprise (SME) sector. Particularly, the study sought to examine the hypothesis in the context of SME buyers and their suppliers. SMEs are particularly relevant to both developed and developing countries. In South Africa, SMEs are perceived to be an engine for growth for both the economy and the community. As such, the study sought to investigate underlying variables that influence the supply chain performance of SMEs for the purpose of identifying ways in which the Sector can improve performance. A conceptual model was developed, drawing from the theory of relational cohesion. Small and Medium Enterprises in the province of Gauteng, South Africa formed the population of the study. Essentially, the predicting roles of knowledge-sharing and business strategy alignment on the supply chain performance of SMEs were evaluated. Furthermore the mediating role of long-term relationship orientation was examined. A survey was conducted in the cities of Johannesburg, Vereeniging and Vanderbijlpark and research data was collected from 341 SMEs. Statistical Package for the Social Sciences (SPSS) 22 was employed to analyse data as well as Analysis of Moment Structures (AMOS) 22 where Structural Equation Modelling (SEM) was undertaken. The results revealed that the research constructs knowledge-sharing, business strategy alignment and long-term relationship orientation influence supply chain performance in a positive way. The findings realized will contribute to the existing body of buyer-supplier relationships literature and increase our knowledge in the field. Pragmatic implications are provided based on the findings as well as recommendations and avenues for future research.
M. Tech. (Logistics, Faculty of Management Sciences) Vaal University of Technology|
Keywords: Business knowledge-sharing; Supply chain performance; 658.7; Entrepreneurship; Business planning; Business logistics